2021
DOI: 10.1007/s10750-021-04726-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the influence of environmental variables on fish assemblages along Tropical Andes: considerations from ecology to conservation

Abstract: The lack of knowledge about freshwater biodiversity in remote areas like montane Andean rivers is noticeable and hinder the development of efficient conservation plans for aquatic ecosystems. Habitat requirements of tropical Andean fishes have been poorly analysed, despite the relevance of these ecological features on the fish conservation strategies. The present study aimed to examine fish assemblages along the altitudinal gradient in tropical Andean rivers and their relationship to habitat features to detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 82 publications
(144 reference statements)
0
1
0
Order By: Relevance
“…The authors concluded that understudied rainforests in Nicaragua should be prioritized for research and biodiversity conservation. Miranda et al (2022), finally, studied the fish assemblages in streams situated along an altitudinal gradient (500-2692 m a.s.l.) in the Andes.…”
mentioning
confidence: 99%
“…The authors concluded that understudied rainforests in Nicaragua should be prioritized for research and biodiversity conservation. Miranda et al (2022), finally, studied the fish assemblages in streams situated along an altitudinal gradient (500-2692 m a.s.l.) in the Andes.…”
mentioning
confidence: 99%